Improved AES for Key Generation In Stream Cipher For MANET Security Application - Sharma, Mansi (Electronics and Communication Engineering Department, 2016)
Mobile ad hoc network comprise of network of nodes which are basically either mobile devices which communicate or routers used for forwarding data to these nodes. MANETs are deployed in many applications such as military services, in collaborative tasks in business environment, localized communication, even in case of emergency situations of disaster relief and rescue operations where infrastructure based networks fails to work or get damaged. However, MANETSs are also vulnerable to various attacks such as Black hole attack, replay attack etc. since there is no boundary predefined for the network and absence of central authority requires each node to participate and manage the network. So, Security of each node and encrypting data transferred through these nodes is the major requirement today’s network. To secure secret information, cryptography comes into the picture where both stream and block ciphers algorithms are preferred. Work related to key generation and various encryption algorithms has been studied. The proposed work includes the improved and optimized (in terms of memory) encrypting algorithm which is derived from AES algorithm. In the improved AES algorithm, on the basis of using Rijndaels substitution box and dynamic shifting principle security is achieved as equivalent to AES. To analyse the security of AES and improved AES, performance analysis is done on the basis of Correlation and Avalanche Effect properties. Also, AES and Improved AES algorithm is used as an application for key generation with some improvements by reducing complexity and producing equivalent randomness for stream cipher because MANETs transmits packets of continuous streams. In the stream cipher overall security depends on randomness of key and Input parameters. So, for each packet random IV is generated and secret key derived from IV using non-linear function to produce randomness in the pseudo ransom number generation procedure for key generation. Moreover, comparative analysis is done with existing A5/1 stream cipher for key stream generation by pseudo random number generator using NIST key generation statistical analysis .The results show that improved AES algorithm provides equivalent security as compared to AES algorithm with less memory and execution time consumable. Also, its application for key generation also passed NIST statistical key generation test
Keywords: MANETs, Security, Key Genertion in Stream Cipher, Improved AES, Initialization vector.